Mutualistic ants as an indirect defence against leaf pathogens. Issue 2 (6th January 2014) - González‐Teuber, Marcia; Kaltenpoth, Martin; Boland, Wilhelm
Summary: Mutualistic ants are commonly considered as an efficient indirect defence against herbivores. Nevertheless, their indirect protective role against plant pathogens has been scarcely investigated. We compared the protective role against pathogens of two different ant partners, a mutualistic and a parasitic ant, on the host plant Acacia hindsii (Fabaceae). The epiphytic bacterial community on leaves was evaluated in the presence and absence of both ant partners by cultivation and by 454 pyrosequencing of the 16S rRNA gene. Pathogen‐inflicted leaf damage, epiphytic bacterial abundance (colony‐forming units) and number of operational taxonomic units (OTUs) were significantly higher in plants inhabited by parasitic ants than in plants inhabited by mutualistic ants. Unifrac unweighted and weighted principal component analyses showed that the bacterial community composition on leaves changed significantly when mutualistic ants were removed from plants or when plants were inhabited by parasitic ants. Direct mechanisms provided by ant‐associated bacteria would contribute to the protective role against pathogens. The results suggest that the indirect defence of mutualistic ants also covers the protection from bacterial plant pathogens. Our findings highlight the importance of considering bacterial partners in ant–plant defensive mutualisms, which can contribute significantly to ant‐mediated protection from plant pathogens.